Analisis kepuasan kerja karyawan bank penkreditan rakyat dilihat dari lingkungan kerja dan kompensasi - Agustina, Dian; Senen, Syamsul Hadi; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2019)
The aim of the research is to find out the influence of work environment on job satisfaction, compensation on job satisfaction, and work environment and compensation on job satisfaction. The object which used as analysis unit in this research were employees of citizenry’s bank X. This research used verifivicative and explanatory survey as method. Data collection techniques is using questionnaires with 25 respondents as sample. The results of this research found that the influence of work environment on  job satisfaction is in the strong category, compensation that affects employee job satisfaction is in the strong category, and work environment and compensation have a strong influence on employee job satisfaction of the citizenry’s bank X. However, this research found that if the condition of work environment is conducive, it will increase employee job satisfaction. On the other hand, if the implementation of compensation goes well, the employee job satisfaction will increase. Moreover, if the condition of work environment is conducive and implementation of compensation goes well, then the job satisfaction of employees citizenry’s bank X will increase